Kronprinzen in der Monarchie der Attaliden? - Habicht, Christian (Gerión. Revista de Historia Antigua, 2006)
The paper briefly discusses how succession worked for the (childless) dynasts of Pergamon and then discusses the cases that occurred once the monarchy had been established. King Attalos I was succeeded by Eumenes II, the eldest of his four sons. Eumenes’own son Attalos, not yet of age at his father’s death, did not follow him at once. Instead, Attalos II succeeded his brother, to be followed after his own death, two decades later, by Attalos III. It is argued that this sequence reflects an agreement between the brothers and that Attalos II was for a time co-ruler of Eumenes, with the title of King.